Preparation and Characterization of Activated Carbon Monoliths with Potential Application as Phenol Adsorbents - Diana Paola Vargas-Delgadillo; Liliana Giraldo; Juan Carlos Moreno-Piraján (E-Journal of Chemistry)
A series of different activated carbons of both honeycomb and disc type were prepared by chemical activation of coconut shells with zinc chloride at different concentrations, without the use of a binder. The structures were characterized by N2 adsorption at 77 K and scanning electron microscopy (SEM), and also some samples were characterized by immersion calorimetry in benzene. These were subsequently used in the adsorption of phenol in aqueous solution. The experimental results indicat that activation with zinc chloride produced a large development of microporosity with a micropore volume of 0.38 to 0.79 cm3 g-1, BET area between 725 and 1523 m2 g-1 and the capacity to adsorb phenol. In addition, the BET and Langmuir models were applied to isotherm data.